2002
DOI: 10.1073/pnas.082096999
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor of Fused represses Gli-mediated transcription by recruiting the SAP18-mSin3 corepressor complex

Abstract: The Suppressor of Fused [Su(fu)] protein plays a conserved role in the regulation of Gli transcription factors of the hedgehog (Hh) signaling pathway that controls cell fate and tissue patterning during development. In both Drosophila and mammals, Su(fu) represses Gli-mediated transcription, but the mode of its action is not completely understood. Recent evidence suggests that Su(fu) physically interacts with the Gli proteins and, when overexpressed, sequesters Gli in the cytoplasm. However, Su(fu) also traver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
194
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(205 citation statements)
references
References 33 publications
(56 reference statements)
6
194
1
Order By: Relevance
“…Fourth, transcriptional activity of Gli molecules is also tightly regulated. Su(Fu) not only prevents nuclear translocation of Gli molecules, but also inhibits Gli1-mediated transcriptional activity (Cheng and Bishop, 2002). Table 1 summarizes major components of the Hh pathway in vertebrates.…”
Section: Signal Transduction Of the Hedgehog Pathwaymentioning
confidence: 99%
“…Fourth, transcriptional activity of Gli molecules is also tightly regulated. Su(Fu) not only prevents nuclear translocation of Gli molecules, but also inhibits Gli1-mediated transcriptional activity (Cheng and Bishop, 2002). Table 1 summarizes major components of the Hh pathway in vertebrates.…”
Section: Signal Transduction Of the Hedgehog Pathwaymentioning
confidence: 99%
“…It is not clear whether this activity requires the functional integrity of primary cilia. In addition, several studies also suggested a nuclear function of Sufu (Cheng and Bishop, 2002;Paces-Fessy et al, 2004), in which Sufu may function as a component of a transcription repressor complex. Regardless of the mode of action, attenuation of Sufu activity through degradation would be an effective way to alleviate the negative inhibition of Sufu on Shh signaling.…”
Section: Ubiquitination-mediated Degradation Of Sufu S Yue Et Almentioning
confidence: 99%
“…Human Sufu expression construct with a myc tag at the carboxyl terminus in pRK5 vector was described earlier (Cheng and Bishop, 2002). The Sufu-K257R mutant was created using the Quickchange site-directed mutagenesis kit (Stratagene, La Jolla, CA, USA).…”
Section: Plasmids and Cell Linesmentioning
confidence: 99%
See 2 more Smart Citations